Strategi Pengembangan Kemampuan Resolusi Konflik Melalui Pembelajaran Sosiologi bagi Peserta Didik Sekolah Menengah Atas - Muh. Hasbi; Siti Komariah; Wilodati Wilodati (Jurnal Paedagogy, 2023)
This study aims to describe strategies for developing conflict resolution skills through sociology learning for high school students. This research method used case studies with a qualitative approach. The informants in this study were sociology teachers, students, and school principals. Informants were selected using a purposive sampling technique. The data collection in this study was carried out by observation, documentation, and in-depth interviews. The data analysis technique of this research used interactive analysis, which includes data reduction, data presentation, and conclusion. Testing the validity of the data in this study used a triangulation technique. The results of this study found that the development of conflict resolution skills through sociology learning for students at SMA Negeri 7 Makassar used the case study method. Students analyzed the cases presented by the teacher to find solutions to the problems of these cases. Through the case study method, students practiced dealing with conflict situations and encouraged them to analyze how to deal with conflicts appropriately to develop conflict resolution abilities.